Strategies to Improve the Transdermal Delivery of Poorly Water-Soluble Non-Steroidal Anti-Inflammatory Drugs - Alexandra Balmanno; James R. Falconer; Halley G. Ravuri; Paul C. Mills (MDPI AG, 2024)
The transdermal delivery of non-steroidal anti-inflammatory drugs (NSAIDs) has the potential to overcome some of the major disadvantages relating to oral NSAID usage, such as gastrointestinal adverse events and compliance. However, the poor solubility of many of the newer NSAIDs creates challenges in incorporating the drugs into formulations suitable for application to skin and may limit transdermal permeation, particularly if the goal is therapeutic systemic drug concentrations. This review is an overview of the various strategies used to increase the solubility of poorly soluble NSAIDs and enhance their permeation through skin, such as the modification of the vehicle, the modification of or bypassing the barrier function of the skin, and using advanced nano-sized formulations. Furthermore, the simple yet highly versatile microemulsion system has been found to be a cost-effective and highly successful technology to deliver poorly water-soluble NSAIDs.